2018
DOI: 10.1111/odi.13002
|View full text |Cite
|
Sign up to set email alerts
|

Novel mutations identified in patients with tooth agenesis by whole‐exome sequencing

Abstract: Objectives To identify potentially pathogenic mutations for tooth agenesis by whole‐exome sequencing. Subjects and Methods Ten Chinese families including five families with ectodermal dysplasia (syndromic tooth agenesis) and five families with selective tooth agenesis were included. Whole‐exome sequencing was performed using genomic DNA. Potentially pathogenic mutations were identified after data filtering and screening. The pathogenicity of novel variants was investigated by segregation analysis, in silico an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 43 publications
(62 reference statements)
0
9
0
Order By: Relevance
“…It is therefore likely that the Eda/Edar cascade regulates another signaling pathway to control the formation and the number of molar teeth, rather than the NF‐κB pathway. Furthermore, many mutations in EDA/ERAD have been shown to cause missing teeth in humans (Clauss et al., 2008, Bergendal, 2014, Zeng et al, 2015, Liu et al., 2018, Zhao et al, 2018). We could not exclude the possibility that the function of EDA/EDAR/EDARADD/NF‐κB pathway in mice is slightly different from that in humans to control the number of teeth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is therefore likely that the Eda/Edar cascade regulates another signaling pathway to control the formation and the number of molar teeth, rather than the NF‐κB pathway. Furthermore, many mutations in EDA/ERAD have been shown to cause missing teeth in humans (Clauss et al., 2008, Bergendal, 2014, Zeng et al, 2015, Liu et al., 2018, Zhao et al, 2018). We could not exclude the possibility that the function of EDA/EDAR/EDARADD/NF‐κB pathway in mice is slightly different from that in humans to control the number of teeth.…”
Section: Discussionmentioning
confidence: 99%
“…Hypohidrotic ectodermal dysplasia patients show dental abnormalities, such as hypodontia, anodontia, malformed teeth, including cone‐ or peg‐shaped teeth, and dental caries (Clauss et al., 2008, Bergendal, 2014, Zeng et al, 2015, Liu, Wang, Qin, Sun, & Zhu, 2018, Zhao et al, 2019). It is likely that dental caries is caused by enamel defects or salivary gland malfunction.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, previous investigations into the impact of syndrome-causing EDA mutations have shown that most syndrome-causing EDA mutations are predicted to cause an elimination of receptor signaling ultimately. However, some observations have indicated that an EDA mutation in a family with X-linked recessive, non-syndromic tooth agenesis, seems to be found that expression, receptor binding and signaling capability of the mutant EDA1 proteins were only impaired, rather than abolished [12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, previous investigations on the impact of syndrome-causing EDA mutations have shown that most syndrome-causing EDA mutations are predicted to ultimately cause receptor signalling to be eliminated. However, some observations of an EDA mutation in a family with Xlinked, recessive, non-syndromic tooth agenesis seem to indicate that the expression, receptor binding and signalling capability of the mutant EDA1 proteins were only impaired rather than abolished [13][14][15].…”
Section: Introductionmentioning
confidence: 99%